Acceleration of Signal Processing Algorithms in Seekers Using Graphics Processing Units - Piotr TUREK (Problemy Mechatroniki)
The paper presents a discussion on the issue of possible acceleration of radiolocation signal processing algorithms in seekers using graphics processing units. A concept and implementation examples of algorithms performing digital data filtering on general purpose central and graphics processing units are introduced. The results of performance comparison of central and graphics processing units during computing discrete convolution are presented at the end of the paper.